A Mesoionic Diselenolene Anion and the Corresponding Radical Dianion. Issue 32 (21st April 2022) - Dong, Zhaowen; Sienkiewicz, Andrzej; Suleymanov, Abdusalom A.; Berton, Cesare; Fadaei‐Tirani, Farzaneh; Scopelliti, Rosario; Severin, Kay
Abstract: Dichalcogenolenes are archetypal redox non‐innocent ligands with numerous applications. Herein, a diselenolene ligand with fundamentally different electronic properties is described. A mesoionic diselenolene was prepared by selenation of a C2‐protected imidazolium salt. This ligand is diamagnetic, which is in contrast to the paramagnetic nature of standard dichalcogenolene monoanions. The new ligand is also redox‐active, as demonstrated by isolation of a stable diselenolene radical dianion. The unique electronic properties of the new ligand give rise to unusual coordination chemistry. Thus, preparation of a hexacoordinate aluminum tris(diselenolene) complex and a Lewis acidic aluminate complex with two ligand‐centered unpaired electrons was achieved. Abstract : Being mesoionic makes the difference : A diselenolene ligand with fundamentally different electronic properties compared to a normal diselenolene is reported. Two stable redox states are accessible: a paramagnetic radical dianion and a diamagnetic monoanion. The ligand was used for the preparation of novel aluminum bis‐ and tris(diselenolene) complexes.